Understanding thin beds within the Bazhenov formation using seismic modeling; IOP Conference Series: Earth and Environmental Science; Vol. 24 : Scientific and Technical Challenges in the Well Drilling Progress, 24–27 November 2014, Tomsk, Russia - Bashirov A. I.; Belozerov V. B. Vladimir Borisovich; Bukhanov N. V. Nikita Vladimirovich; Evdokimov A. V. (2015, 2015)
Title screen